Study of Microplastic Contamination in the Digestive Organs of Parrotfish (Scarus rivulatus) Caught in Ekas Bay - Sumsanto, Muhammad; Diniariwisan, Damai (Journal of Fish Health, 2024)
Microplastics have become a major concern in global environmental research due to their significant impact on marine ecosystems. Microplastic pollution has been detected in almost all aquatic environments, including oceans, rivers and lakes. This study aims to evaluate the level of microplastic contamination in the digestive organs of old parrot fish caught in Ekas Bay. Focusing on the digestive organs is important because ingested microplastics can have detrimental effects on fish health, including digestive disorders and bioaccumulation of harmful chemicals. The research method used was descriptive with a sample size of six parrot fish. Based on research conducted on the digestive organs of parrot fish, it was found that the types of microplastics found were in the form of fragments, films, pellets and fibers. The total abundance of microplastics in the intestinal organs ranges from 290 par/gr to 410 par/gr, while in the stomach organs it is 272 par/gr to 310 par/gr. The highest percentage of microplastics in the intestinal organs was pellets at 47% and in the stomach organs it was fragments at 54%.